2020
DOI: 10.1021/acs.biomac.0c00726
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Morphology on the Properties of Biodegradable Nanoparticles and Their Diffusion in Complex Biological Medium

Abstract: Nanoparticle morphology (size, shape, and composition) and surface chemistry are the determining factors underpinning the efficacy of such materials in therapeutic applications. The size, shape, and surface chemistry of a nanoparticle can strongly influence key properties such as interactions with diverse biological fluids and interfaces and, in turn, impact the delivery of bioactive cargo, modulating therapeutic performance. This is exemplified in ocular drug delivery, where potential therapeutics must naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…Our recent ex vivo study demonstrated retinal permeation of small liposomes and tubular polymersomes [20,29]. Small particle size and non-viscous polymersome formulations enable use of small injection needles (in this study 30 G), representing another clinical advantage compared to the implants.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our recent ex vivo study demonstrated retinal permeation of small liposomes and tubular polymersomes [20,29]. Small particle size and non-viscous polymersome formulations enable use of small injection needles (in this study 30 G), representing another clinical advantage compared to the implants.…”
Section: Discussionmentioning
confidence: 71%
“…The mean molecular weights (M n ) of all PPP copolymers for polymersomes were in the range of 10.4-14.4 kDa, and polydispersities were 1.13-1.23. The properties of PEG-PTMC polymers for polymeric micelles were described previously [20].…”
Section: Characterization Of Polymeric Micelles and Polymersomesmentioning
confidence: 99%
“…Moreover, the small size of PLGA NPs and their surface-modified forms may offer several advantages like low toxicity, improved solubility, high surface area, dissolution rate and enhanced biodistribution. 40 42
Figure 6 Particle size distribution and zeta potential of ( A ) PLGA NPs, ( B ) 2-HP-β-CD/PLGA NPs, ( C ) trehalose/PLGA NPs, ( D ) chitosan oligosaccharide/PLGA NPs.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the small size of PLGA NPs and their surface-modified forms may offer several advantages like low toxicity, improved solubility, high surface area, dissolution rate and enhanced biodistribution. [40][41][42] The zeta potential of the PLGA, 2-HP-β-CD/PLGA, trehalose/PLGA and chitosan oligosaccharide/PLGA NPs were (−22.46 ± 4.76), (−19.09 ± 1.99), (−16.24 ± 4.65) and (−7.12 ± 0.75) mV respectively. Since the surface…”
mentioning
confidence: 99%
“…As an illustration, the morphology of nanoparticles can be attributed to their properties, such as toxicity in biological applications [19]. Also, the structure and morphology of nanoparticles can influence the interaction of nanoparticles with biological fluids and interfaces and, finally, on the performance of nanoparticles in the body [50]. The surface morphology of MOFs can be investigated using SEM and FESEM (field emission scanning electron microscope) methods, and the inner structure of particles can be studied using TEM (transmission electron microscopy) [13].…”
Section: Morphologymentioning
confidence: 99%